Validade da ação fiscalizatória legal no uso e recomendação de agrotóxicos na fronteira oeste do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Brazil is one of the largest pesticides consumers on the planet, however, studies point to lack of oversight and guidance on the use of pesticides and claim that this is the way to reduce the number of infractions. The objective of this study was to verify the role of the oversight in the awareness of the use of pesticides in West Frontier of Rio Grande do Sul, before and after the guidelines of the supervisory organ, seeking to identify and evaluate the effective actuation of the public organ regarding compliance with the legislation. During the harvest times of 2014/15 and 2015/16 data from inspections of producers and traders were grouped, seeking for information related to the present situation of pesticide use in the region, such data were obtained from the State Department of Agriculture reports. The first crop data corresponds to a period where there was no oversight or revious guidance, due the absence of service, and the next harvest data corresponds to a prior oversight process. The technical managers and the producers were assessed, comparing the number of irregularities related to pesticide legislation ascertained in each harvest. After the guidelines, there was a reduction of the number of infractions by property, increase of producers without infractions and significant reduction of infractions by the use of pesticides in disagreement with the agronomic prescription. Regarding the issue of prescriptions by the technical managers, there was a marked decrease of irregularities from the first to the second harvest assessed. It is concluded that the guidelines of the supervisory organ presented positive results on reducing infactions of the pesticide laws, but there is need to continue these actions with producers and technicians managers, seeking adequacy and compliance with legislation.
Keywords: Receita agronômica; Fiscalização agropecuária; Lei Federal 7802/89; Agronomic prescription; Agricultural inspection; Federal Law 7802/89; CNPQ::CIENCIAS AGRARIAS